2021
DOI: 10.3390/nu13103447
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Interventions to Prevent Childhood Obesity: A Literature Review

Abstract: Several dietary interventions have been conducted to prevent/reduce childhood obesity, but most of them are known to have failed in tackling the obesity epidemic. This study aimed to review the existing literature on dietary interventions for the prevention of childhood obesity and their effectiveness. A literature search was conducted using PubMed Central®. Only articles published between 2009 and 2021, written in English, conducted in humans, and including children and/or adolescents (<18 years old) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
1
33
0
2
Order By: Relevance
“…All interventions described an improvement in liver outcomes in conjunction with weight loss ( 4 ). It is known that it is very difficult to achieve clinically relevant and lasting body weight reduction in children and adolescents with obesity or extreme obesity by lifestyle intervention ( 5 , 6 ). Since the effective treatment of NAFLD by lifestyle modification has no sustainable effect, the search for pharmacological agents is of high relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All interventions described an improvement in liver outcomes in conjunction with weight loss ( 4 ). It is known that it is very difficult to achieve clinically relevant and lasting body weight reduction in children and adolescents with obesity or extreme obesity by lifestyle intervention ( 5 , 6 ). Since the effective treatment of NAFLD by lifestyle modification has no sustainable effect, the search for pharmacological agents is of high relevance.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published review demonstrated, that the positive effects of a lifestyle intervention on liver-associated parameters are weak and are strongly associated with body weight loss ( 4 ). Since lifestyle interventions are largely unsuccessful in achieving and maintaining clinically meaningful weight loss ( 5 , 6 ), the search for new pharmacological interventions in adults and children with NAFLD is on focus. One possible approach would be to further investigate the role of the adipokine leptin in relation to the development of NAFLD ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of seven school-based nutrition programmes seeking to increase F&V consumption has shown weaker results [ 46 ] than those of this study. Ultimately, a recent literature review to report the effectiveness of dietary interventions in childhood obesity published between 2009 and 2021, discloses that a large number of studies, mainly based on school interventions, did not show any results or did not obtain effective results [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and overweight are often blatantly ignored and delay early intervention, which inevitably increases the risk of significant health hazards 78 . In addition to behavioral and dietary recommendations, changes in the community-based interventions are crucial measures 79,80 .…”
mentioning
confidence: 99%